Notes sobre la confluència de «v» i «b» en català - Moran, Josep (Caplletra. Revista Internacional de Filologia, 2015)
The author first reviews the existing literature on the topic, and then shows how the phonetic similarity between -b- and -v- and their lack of functional load, with the addition of Basque influence, lead to the leveling of the two phonemes.